Worldwide interethnic variability and geographical distribution of CYP2C9 genotypes and phenotypes - Céspedes-Garro, Carolina; Fricke-Galindo, Ingrid; Naranjo, María Eugenia G; Rodrigues-Soares, Fernanda; Fariñas, Humberto; de Andrés, Fernando; López-López, Marisol; Peñas-Lledó, Eva M; LLerena, Adrián (Expert opinion on drug metabolism & toxicology, 2015)
Notably differences in CYP2C9 allele frequencies among worldwide populations have been reported, with an interesting low frequency of the CYP2C9*2 allele in Amerindians compared with Admixed and European populations. Literature was searched using the PubMed database and was focused on worldwide original research papers on CYP2C9 alleles and CYP2C9 phenotypes ("predicted" from CYP2C9 genotypes and "measured" metabolic phenotype with a probe drug) among healthy volunteers according to their ethnicity and geographical distribution. Seventy-eight original research articles including a total of 31,978 subjects were identified. CYP2C9*2 allele is the most frequent in Caucasian populations (average 14%), with the lowest frequencies for Africans (0.46%), East Asians (0.56%) and Native Americans (1.25%), which is in agreement with the hypothesis about the low prevalence in Amerindians. CYP2C9*3 shows the highest frequency among South Asians (11.7%), while CYP2C9*5 (1.56%) and *8 (4.70%) in African Americans. The predicted poor metabolizers (gPMs) were found overall in a low frequency, with the highest frequency detected for South Asians, in accordance with the CYP2C9*3 frequency in these populations. This study shows the worldwide variability in the CYP2C9 allele frequencies across different ethnic and geographic groups. Data about CYP2C9 "measured" metabolic phenotypes is still limited.